2014
DOI: 10.1140/epja/i2014-14020-3
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry energy in nuclear density functional theory

Abstract: Abstract. The nuclear symmetry energy represents a response to the neutron-proton asymmetry. In this paper we discuss various aspects of symmetry energy in the framework of nuclear density functional theory, considering both non-relativistic and relativistic self-consistent mean-field realizations side by side. Key observables pertaining to bulk nucleonic matter and finite nuclei are reviewed. Constraints on the symmetry energy and correlations between observables and symmetry energy parameters, using statisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 99 publications
(185 reference statements)
5
65
0
1
Order By: Relevance
“…However, other correlations shown in the literature with E sym or K sym [11,47] are not observed here, which might again indicate the model dependence of these correlations.…”
Section: B Correlationssupporting
confidence: 50%
See 2 more Smart Citations
“…However, other correlations shown in the literature with E sym or K sym [11,47] are not observed here, which might again indicate the model dependence of these correlations.…”
Section: B Correlationssupporting
confidence: 50%
“…As a consequence, the different EoS parameters extracted from the data fit exhibit strong correlations [10][11][12][13]. Some of these correlations might reflect physical properties of the EoS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows to consider the NMP also as model parameters. This is a more intuitive way to communicate the model parameters and it allow direct comparison with other mean-field models which are often also fully mappable to NMP, see for example the comparison of symmetry energies in [56]. isoscalar ground state properties equilibrium density:…”
Section: Homogeneous Nuclear Mattermentioning
confidence: 99%
“…In the meantime, parametrizations have been steadily developed further including more and more data and exploiting the benefits of the χ 2 techniques, for recent examples see, e.g., [7,8]. The availability of these thoroughly fitted parametrizations allowed a series of extensive studies of correlations within the models using covariance analysis which revealed interesting inter-relations between symmetry energy, neutron radius, and dipole spectra [9,10,11,12]. In this paper, we want to discuss error analysis from a more general perspective.…”
Section: Introductionmentioning
confidence: 99%